CORTICAL DYSARTHRIA: PATHOGENESIS, CLINICAL MANIFESTATIONS, AND CORRECTIVE APPROACHES - Iminjonova Mokhichehra Alimardon qizi (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
ABSTRACT: This article systematically examines the mechanisms of cortical dysarthria, namely its pathogenesis, and speech disorders resulting from damage to the speech motor areas in the cerebral cortex. The main clinical signs of cortical dysarthria - imprecise articulation, disruption of speech tempo and rhythm, weakening of sound production processes, and impairment of complex articulatory movements - are analyzed on a scientific and theoretical basis. Information is also provided on corrective approaches used in speech therapy practice, including articulation exercises, breathing and speech coordination techniques, strengthening of phonetic and phonemic skills, and the effectiveness of neuropedagogical methods. The research findings have practical significance for speech therapists, special education teachers, and practitioners working with cortical dysarthria.